The guardian : perspectives on the Ministry of Finance of Ontario - Dutil, Patrice A., 1960- (Institute of Public Administration of Canada series in public management and governance., 2011)
"Finance departments have often been portrayed as guardians of the public purse. In The Guardian, a multidisciplinary group of contributors examines the Ministry of Finance of Ontario since the Second World War. During the last sixty years the Ministry was transformed from a relatively small 'Treasury' to a sophisticated policy machine. What started as a modest bookkeeping operation evolved into a key bureaucratic and policy agency as the government of Ontario assumed a leadership position in developing the province.